Inovasi Layanan Kepegawaian Berbasis E-Government Melalui Sistem Informasi Terintegrasi Manajemen ASN (Sigma) di KantorBadan Kepegawaian Daerah Provinsi Riau - Fernanda Ayesha; Fitria Ramadhani Agusti Nst (Al-Manar Journal of Public Administration and Management, 2024)
This study aims to describe the innovation of E-Government-based personnel services through the ASN management information system (SIGMA) at the Riau Province Regional Personnel Agency Office. The data analysis technique used is qualitative descriptive analysis, which describes specific things obtained through data, interviews and documentation. The results of the study state that the innovation of E-Government-based personnel services through the ASN management information system (Sigma) at the Riau Province Regional Personnel Agency office is not optimal, as can be seen from several indicators that have not been running optimally, namely there is one feature that cannot be used which is currently still in the development stage, there are features that are locked because the feature is not yet suitable for use, and there is no legal umbrella that has been approved for this Sigma application. The inhibiting factors are that IT employees are not optimal in developing features, employees are still in a hurry to create features which result in the features created not being able to be used, and the Governor's regulation has not been issued which will be the legal umbrella for the Sigma application.